Curtain Grouting Test On Volcanic Breccia Foundation As An Effort To Assess The Effectiveness Of Grouting Case Study: Construction Of Minting Dam - Ujang Kurdiawan; Yusron Saadi; Muhajirah Muhajirah (Publikasi Indonesia, 2023)
Meninting Dam is located on the Meninting River, Meninting Watershed WS Lombok. Administratively, the location of this dam is located in Bukit Tinggi Village, Gunungsari District, and Gegerung Village, Lingsar District, West Lombok Regency. It is planned that Meninting Dam has a height of 79 m, the type of Urugan Zonal Random Dam with Upright Core, with a maximum storage capacity of 12.18 million m3 and an average storage capacity of 9.91 million m3. From the results of geological investigations during planning and pre-construction geological investigations, it is known that the body of the Meninting Dam will rest on a foundation in the form of volcanic breccia rock. Given that Meninting Dam has a reasonably high height, the foundation rock's quality is essential in terms of foundation permeability and the ability of the foundation rock to support the dam above it. On the left backrest, there is a volcanic breccia layer with a lousy level of cementation, which affects the high permeability value of the layer. In order to reduce the permeability value, it is necessary to conduct curtain grouting experiments to determine the extent of grouting effectiveness to reduce the permeability value and improve the overall foundation. The results of curtain grouting experiments and cement injection showed that the average incoming cement per meter was 21.43 kg / m or classified as efficient with a mixture change of 1 4. The effectiveness of grouting in poorly cemented volcanic breccia in Check Hole (CH) against Pilot Hole (G1) with an average of = 65% or classified as GOOD (Good) and seen semi-logarithmetically the significant decline of Lugeon towards target < 3 according to technical specifications.